Hak Kreditur Baru Atas Objek Hak Tanggungan Yang Diperoleh Dari Cessie Jika Debitur Wanprestasi - Muhammad, Faishal; Arsin Lukman, Fransiscus Xaverius (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Credit agreements between banks as creditors often use land rights as collateral for the credit agreement. Sometimes it is found that the debtor defaults or defaults by not paying bills on time several times due. In some cases for the bank's financial soundness, the bank sells receivables or collection rights to other parties. Selling receivables to other parties is what is called the transfer of receivables or Cessie. By transferring the right to collect from the old creditor to the new creditor, the debtor's obligation to pay off the debt to the new creditor is also transferred. The thing that can be a problem is if there is a default by the debtor. Execution and what rights are the rights of new creditors to protect themselves from losses. Based on these problems, the author examines the discussion of how the New Creditor's Rights Over the Object of Mortgage Obtained from Cessie If the Debtor Defaults and What is the procedure for cessie creditors against third parties as new creditors. The author uses the method of quantitative juridical data analysis, namely as a way to draw conclusions from the collected research results. Juridical, given that this research is based on existing laws and regulations as normative legal norms. Quantitative, more sensitive and able to adapt to many sharpening of shared influence on the patterns of values encountered. Particularly with regard to the position of cessie regulations without the consent and knowledge of the debtor linked to the Civil Code and creditor cessie procedures for third parties as new creditors based on the Civil Code which is guaranteed.